Social perception on mental illness - Sandu, Mihaela Luminita; Rus, Mihaela; Tasente, Tanase; Djellouli Zine (Technium Social Sciences Journal, 2020)
Psychiatric disorders are among the top of the conditions that cause disability worldwide and attract one of the highest levels of stigmatization in today’s society, which has a strong impact on the quality of life of patients suffering from these conditions. In Romania, mental health develops more difficult than the other medical and social sciences due not to the lack of professionals or lack of interest of the scientific community, but because it still carries the stigma of "madness". This stigma gives him a gloomy aura and over time has led to profound prejudices related to both the beneficiaries of mental health services and their specialists. Many people who need or want to call for services in the field of mental health, refuse or fear to appeal to specialists for fear of stigma and prejudice. Due to these prejudices, the society is reluctant to integrate people who have suffered from a mental illness, they are often stigmatized and rejected by others, being viewed with suspicion due in particular to the unpredictability of its potentially antisocial behaviors and actions. The reason that justifies this research is that by determining the way in which psychic patients are perceived, the interest with which the society relates to their problems is highlighted. The results obtained have a practical involvement in the sense that it demonstrates the necessity and usefulness of informing the general population about mental illness. By correct information it is envisaged to change the attitude towards the illness and the mentally ill, thus preventing their stigmatization and discrimination.